When Female (Male) Robot Is Talking To Me: Effect of service robots’ gender and anthropomorphism on customer satisfaction - Seo, Soobin (International journal of hospitality management, 2022)
Along with the popularity of service robots in various service settings, service robots are often gendered as either female or male. This study examines the role of service robots’ gender and level of anthropomorphism of service robots on pleasure and customer satisfaction at service encounters. A 2 gender of service robots (female/male) X 2 level of anthropomorphism (low/high) between-subject factorial design is employed to test hypotheses using a scenario-based experimental survey. Results of the proposed moderated mediation model suggests that female service robots generated more pleasure and higher satisfaction compared to that of male service robots, and its influence is amplified when the level of anthropomorphism is high rather than low. Findings highlight the benefit of female service robots in a hotel setting which is only effective when the service robot is humanized, which provides useful guidelines for hoteliers when applying service robots in their service settings. •This study examines the role of service robot’s gender and level of anthropomorphism on customers’ responses.•A 2 (service robot’s gender) X 2 (level of anthropomorphism) between-subject experimental design is used for the study.•Customers show a higher satisfaction towards a female service robot than male robot only when the robot is humanized.•Moderated mediation model evidence pleasure as a mediator between service robot’s gender and customer satisfaction.